2014
DOI: 10.1016/j.patrec.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

3D people surveillance on range data sequences of a rotating Lidar

Abstract: In this paper, we propose an approach on real-time 3D people surveillance, with probabilistic foreground modeling, multiple person tracking and on-line re-identification. Our principal aim is to demonstrate the capabilities of a special range sensor, called rotating multi-beam (RMB) Lidar, as a future possible surveillance camera. We present methodological contributions in two key issues. First, we introduce a hybrid 2D-3D method for robust foreground-background classification of the recorded RMB-Lidar point c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…Nowadays, this term could be associated with using 3D/2.5D data acquisition equipment [6] like time-of-flight (ToF) cameras, structured light sensors, stereo cameras, laser scanners (LiDARs) [7], and Flash Ladars [8] in video surveillance. Availability of 3D data acquisition equipment leads to considerable progress in video surveillance related research areas such as background subtraction and tracking people [9], [10], person identification [11], [12], face recognition [13], posture recognition [14], [15], gesture recognition [16], people counting [17], human activity recognition [18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, this term could be associated with using 3D/2.5D data acquisition equipment [6] like time-of-flight (ToF) cameras, structured light sensors, stereo cameras, laser scanners (LiDARs) [7], and Flash Ladars [8] in video surveillance. Availability of 3D data acquisition equipment leads to considerable progress in video surveillance related research areas such as background subtraction and tracking people [9], [10], person identification [11], [12], face recognition [13], posture recognition [14], [15], gesture recognition [16], people counting [17], human activity recognition [18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In such point clouds view invariance can be simulated with proper 3D transformations of the point cloud of each person (Benedek et al, 2016), while occlusion handling, background segmentation and people tracking can also be more efficiently implemented in the range image domain, than with optical images. (Benedek, 2014) showed that a 64-beam LiDAR (Velodne HDL-64E) is able track several people in realistic outdoor surveillance scenarios, and (Benedek et al, 2016) showed that the same sensor is also effective in the re-identification of people leaving and re-entering the field-of-view. However, the 64-beam sensor is too heavy and expensive for wide usage in surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
“…(Fuerstenberg and Lages, 2003) and (Gidel et al, 2010) have implemented a system tested in passenger car using laser methods. (Lovas and Barsi, 2015) applied profile laser scanner, (Benedek, 2014) has used rotating multi-beam laser scanner to detect pedestrians. (Gate and Nashashibi, 2008) have improved the pedestrian classification accuracy by recursive estimation.…”
Section: Introductionmentioning
confidence: 99%